Market intelligence for informing crop-breeding decisions by CGIAR and NARES - Donovan, Jason A.; Coaldrake, Peter; Rutsaert, Pieter; Banziger, Marianne; Mbugua-Gitonga, A.; Naziri, D.; Newby, J.; Ndegwa, Michael K.; Demont, Matty (CGIAR System Organization, 2022)
Crop breeding by the Consultative Group on International Agricultural Research (CGIAR), in partnership with national agricultural research and extension systems (NARES) and privately owned seed companies, forms the backbone of the research and development (R&D) effort needed to ensure future food security in developing regions. Over the past decades, varieties derived from CGIAR germplasm have helped provide food for hundreds of millions living in harsh and vulnerable environments. However, the capacity to deliver increased benefits from crop breeding will depend on effective strategies to address the stubbornly slow rate of uptake of improved varieties. Meeting the challengewill require, among other inputs, deeper insights on the evolving preferences and requirements of farmers, processors and consumers. In short, breeding will need to be led more by demand. Key to the success of demand-led breeding will be the availability of reliable and timely intelligence on the current and future preferences and requirements of farmers, processors and consumers. Although ‘market intelligence’ has existed in various forms in CGIAR’s social science research agenda, an opportunity exists for increased relevance based on shared approaches and tools and new partnerships, both within CGIAR and between CGIAR and its partners. Beginning in 2022, a coordinated effort through the CGIAR Initiative on Market Intelligence looks to build cross-functional and transdisciplinary teams to provide market intelligence in support of crop breeding and seed-system development.